Fundamental And Technical Factors Towards Investment Decisions And Company Value Moderated By Sales At Trading Companies In Indonesia - Mamay Komarudin (International Journal of Science, Technology & Management, 2021)
The purpose of this study is a) to analyze the influence of fundamental factors, namely profit growth, ROE and DER on investment decisions and value; to analyze the influence of macro factors namely sectoral PDP, SBI and exchange rate and beta of stocks on investment decisions and company value; to analyze the influence of technical factors i.e. the previous share price and trading volume on investment desperedness and the value of the company; to analyze the effect of investment decisions on the company's value; to analyze sales as moderating the effect of investment decisions on the value of the company. Based on the results of data analysis and discussion, it can be concluded that 1) fundamental factors as measured by profit growth, ROE and DER affect investment decisions; 2) Macro variables, namely interest rates and sectoral GDP, have a significant effect on investment decisions. That means higher macro variables are causing increases and decreases in investment decisions. While inflation has no positive and significant effect; 3) Technical variables consist of the previous share price and the trading volume has no significant effect on investment decisions. That means the higher the previous share price and the volume of trades does not increase investment decisions; 5) Fundamental factors namely profit growth, ROE and DER affect the value of the company; 6) Macro variables namely interest rates and sectoral GDP and inflation have no significant effect on the value of the company; 7) Investment decisions affect the value of the company; 8) In sales is not proven to moderate the mover of investment decisions against the value of the company.